Ochrona i bezpieczeństwo danych osobowych w organizacji - Bajorek, Jacek (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The current laws govern the admissibility of the personal data processing in ICT systems and determine appropriate levels of protection of such information. Entrusted with the protection of personal data, in any organization processing personal data, is the administrator of personal data, who can determine the information security administrator to carry out these tasks.